Conservation concerns associated with low genetic diversity for K’gari–Fraser Island dingoes - G. C. Conroy (Nature Portfolio, 2021)
Abstract The dingo population on world heritage-listed K’gari-Fraser Island (K’gari) is amongst the most well-known in Australia. However, an absence of population genetic data limits capacity for informed conservation management. We used 9 microsatellite loci to compare the levels of genetic diversity and genetic structure of 175 K’gari dingo tissue samples with 264 samples from adjacent mainland regions. Our results demonstrated that the K'gari population has significantly lower genetic diversity than mainland dingoes (A R , H E , P AR ; p < 0.05) with a fourfold reduction in effective population size (N e  = 25.7 vs 103.8). There is also strong evidence of genetic differentiation between the island and mainland populations. These results are in accordance with genetic theory for small, isolated, island populations, and most likely the result of low initial diversity and founder effects such as bottlenecks leading to decreased diversity and drift. As the first study to incorporate a large sample set of K’gari dingoes, this provides invaluable baseline data for future research, which should incorporate genetic and demographic monitoring to ensure long-term persistence. Given that human-associated activities will continue to result in dingo mortality, it is critical that genetic factors are considered in conservation management decisions to avoid deleterious consequences for this iconic dingo population.